Absence of canonical trophic levels in a microbial mat. Issue 5 (13th July 2022) - Gonzalez‐Nayeck, Ana C.; Mohr, Wiebke; Tang, Tiantian; Sattin, Sarah; Parenteau, M. Niki; Jahnke, Linda L.; Pearson, Ann
Abstract: In modern ecosystems, the carbon stable isotope (δ 13 C) ratios of consumers generally conform to the principle "you are what you eat, +1‰." However, this metric may not apply to microbial mat systems where diverse communities, using a variety of carbon substrates via multiple assimilation pathways, live in close physical association and phagocytosis is minimal or absent. To interpret the δ 13 C record of the Proterozoic and early Paleozoic, when mat‐based productivity likely was widespread, it is necessary to understand how a microbially driven producer–consumer structure affects the δ 13 C compositions of biomass and preservable lipids. Protein Stable Isotope Fingerprinting (P‐SIF) is a recently developed method that allows measurement of the δ 13 C values of whole proteins, separated from environmental samples and identified taxonomically via proteomics. Here, we use P‐SIF to determine the trophic relationships in a microbial mat sample from Chocolate Pots Hot Springs, Yellowstone National Park (YNP), USA. In this mat, proteins from heterotrophic bacteria are indistinguishable from cyanobacterial proteins, indicating that "you are what you eat, +1‰" is not applicable. To explain this finding, we hypothesize that sugar production and consumption dominate the net ecosystem metabolism, yielding a community in which producers and consumers share primary photosynthate as a common resource. This idea was validated by confirming that glucose moieties in exopolysaccharide were equal in δ 13 C composition to both cyanobacterial and heterotrophic proteins, and by confirming that highly 13 C‐depleted fatty acids (FAs) of Cyanobacteria dominate the lipid pool, consistent with flux‐balance expectations for systems that overproduce primary photosynthate. Overall, the results confirm that the δ 13 C composition of microbial biomass and lipids is tied to specific metabolites, rather than to autotrophy versus heterotrophy or to individual trophic levels. Therefore, we suggest that aerobic microbial heterotrophy is simply a case of "you are what you eat."